SSR-marker Based Genetic Diversity In Sri Lankan Traditional Maize (Zea Mays L.) Accessions (SAARC Journal of Agriculture, 2024)
The beneficial alleles possessed by maize landraces are valuable resources for improving novel climate resilient maize varieties via crop breeding initiatives. Therefore, this study investigated the genetic diversity of 20 traditional maize accessions of Sri Lanka using five SSR markers (umc1545, bnlg1627, umc1342, bnlg105 and bnlg1564). A total of 35 alleles were identified by all the SSR markers, with observed allele numbers ranging from 4 (umc1545) to 10 (bnlg1627). The higher values of effective number of alleles, observed heterozygosity, and expected heterozygosity for markers bnlg1627 and bnlg1564 suggest their potential as key contributors in identifying the genetic variability within the maize accessions. The Polymorphism Information Content (PIC) values ranged from 0.670 to 0.827 with a mean value of 0.735, further highlighting the informativeness of the markers. Considering the genetic diversity among the accessions, SEU6, SEU20, and SEU23 consistently displayed higher levels in their genetic diversity values while the genetic dissimilarity values ranged from 0.1 to 1.0 with the mean value of 0.81. The accessions SEU3 and SEU4 were closely linked among the pairwise combinations. Further, the cluster analysis identified five clusters of Sri Lankan maize accessions. Based on the results of this study, SEU6 and SEU20 can be the potential candidates for conservation and beneficial for the adaptability of maize to changing environments. These results can pave the way for targeted maize breeding strategies and highlight the need for continued efforts in improving food, feed and forage industries, with implications for enhancing crop resilience and sustainable agricultural development.SAARC J. Agric., 22(1): 45-58 (2024)